Static vs dinamic short nail in pertrochanteric fractures: experience of two center in Northern Italy - quattrini, fabrizio; ortolani, alessandro; ciatti, corrado; puma pagliarello, calogero; martucci, antonio; gurrieri, luca; stallone, stefano; melucci, giuseppe; domenico, tigani; Maniscalco, Pietro (Acta Biomedica Atenei Parmensis, 2021)
Background: Lateral fractures of proximal femur are the most frequent to treat for the traumatologist surgeon. Intramedullary nailing is the gold standard treatment of this type of fracture. The aim of the study is to analyze the results obtained with the Elos Intrauma nail by the experience of two Departments of Orthopedics and Traumatology ("Guglielmo da Saliceto" Hospital in Piacenza and the Maggiore hospital in Bologna).METHODS:We performed a retrospective cohort study of 400 patients with lateral femoral neck fracture surgically treated with Elos Intrauma standard nail. The examined period is from 1st Jannuary 2018 to 31st Dicember 2020. In all patients we implanted Elos® - Intrauma nail, a titanium cervical diaphyseal nail, according to the standard technique.RESULTS: We evaluate at a minumum of three months of follow up 286/400 patients. Average follow up was 3.94 months, minimum 3 months and maximum 24 months. We obtain the 96.85 % of fracture healing, recording 33 complications (11.54%). The incidence of surgical revision was 2.8% (8 cases). No mechanical complications was found in stable fractures treated with short nail and without distal locking.CONCLUSIONS: With the use of Elos nail we obtained 95% of radiographic healings within three months with a complication rate comparable to literature report. Distal locking is absolutely recommended in complex fractures, it may be superfluous after careful evaluation of the fracture pattern and morphological characteristics of the femur to be treated; future in-depth studies may narrow the criteria to choose distal locking or non locking.